2017
DOI: 10.1007/s00412-017-0637-6
|View full text |Cite
|
Sign up to set email alerts
|

UsnRNP biogenesis: mechanisms and regulation

Abstract: Macromolecular complexes composed of proteins or proteins and nucleic acids rather than individual macromolecules mediate many cellular activities. Maintenance of these activities is essential for cell viability and requires the coordinated production of the individual complex components as well as their faithful incorporation into functional entities. Failure of complex assembly may have fatal consequences and can cause severe diseases. While many macromolecular complexes can form spontaneously in vitro, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 156 publications
2
53
0
Order By: Relevance
“…SMA is most commonly caused by reduced levels of the Survival Motor Neuron (SMN) protein which in humans is encoded by two genes, SMN1 and SMN2 (Lefebvre et al, 1995). SMN is ubiquitously expressed and canonically functions in assembly of spliceosomal snRNPs Matera and Wang, 2014;Gruss et al, 2017). SMN is also reported to have other functions related to RNA trafficking, translation, endocytosis, cytoskeletal maintenance, and cellular signaling (Raimer et al, 2017;Singh et al, 2017;Chaytow et al, 2018;Price et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SMA is most commonly caused by reduced levels of the Survival Motor Neuron (SMN) protein which in humans is encoded by two genes, SMN1 and SMN2 (Lefebvre et al, 1995). SMN is ubiquitously expressed and canonically functions in assembly of spliceosomal snRNPs Matera and Wang, 2014;Gruss et al, 2017). SMN is also reported to have other functions related to RNA trafficking, translation, endocytosis, cytoskeletal maintenance, and cellular signaling (Raimer et al, 2017;Singh et al, 2017;Chaytow et al, 2018;Price et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the mTOR complexes, mTORC1, promotes mRNA translation and elongation through ribosomal protein S6 kinase 1 (S6K1) and eukaryotic translation initiation factor 4E (eIF4E)-binding protein 1 (4E-BP1) as well as by increasing rRNA and tRNA transcription 49 . Some evidence also suggests the involvement of the mTORC1 complex in U-snRNP biogenesis 50 . Taken together, the striking upregulation of all of the above classes of sncRNAs in CSF cells, particularly in the relapse phase, is consistent with activation of mTOR signaling in activated and proliferating cells enriched in the target organ.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that SMN recruits TGS1 favoring its engagement with the m7G-capped snRNA bound to the Sm ring, so as to allow hypermethylation of the cap (Mouaikel et al, 2003b;Mouaikel et al, 2002). The TMG cap and the Sm ring are thought to act as a bipartite nuclear-localization signal that mediates nuclear import of the snRNP particles (Gruss et al, 2017;Hamm et al, 1990;Narayanan et al, 2004;Natalizio and Matera, 2013). Work in Drosophila has shown that that dTgs1 interacts with the Gemin3 subunit of the SMN complex in a two-hybrid assay (Borg et al, 2016).…”
Section: The Biochemical Relationships Between Tgs1 and Smnmentioning
confidence: 99%
“…Once in the cytoplasm, snRNAs associate with the Sm protein complex that physically binds TGS1 through its SmB component (Mouaikel et al, 2003b;Mouaikel et al, 2002). The seven Sm core proteins assemble into a heteroheptameric donut-shaped multiprotein structure that binds the U1, U2, U4 and U5 snRNAs, forming four of the five snRNP subunits of the spliceosome (Gruss et al, 2017). The assembly of the Sm-snRNA particles is chaperoned by the survival of motor neurons (SMN) complex, which includes SMN, Gemin2-8 and Unrip/STRAP (Carissimi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation